2018
DOI: 10.3390/ma11101827
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Osteoblasts on Laser-Modified Nanostructured Titanium Surfaces

Abstract: Nanostructured titanium has become a useful material for biomedical applications such as dental implants. Certain surface properties (grain size, roughness, wettability) are highly expected to promote cell adhesion and osseointegration. The aim of this study was to compare the biocompatibilities of several titanium materials using human osteoblast cell line hFOB 1.19. Eight different types of specimens were examined: machined commercially pure grade 2 (cpTi2) and 4 (cpTi4) titanium, nanostructured titanium of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Marginal bone loss can be influenced by other factors than implant-pillar connection, including other technical differences such as implant design, 62 reduced platform, 41,63,64 micron-sized gap position 18,65 and surface treatment. 66,67,68,69 These factors combined, may have directly influenced the ΔMBL 16 and the heterogeneity of the results of the present systematic review of the literature. According to the retrospective study recently published by Galindo-Moreno et al, 62 the microstructure or the design of the implant adversely impacted the ΔMBL in peri-implant areas, possibly due to the generation of unbalanced tensile forces in the long-axis of the implant fixture.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Marginal bone loss can be influenced by other factors than implant-pillar connection, including other technical differences such as implant design, 62 reduced platform, 41,63,64 micron-sized gap position 18,65 and surface treatment. 66,67,68,69 These factors combined, may have directly influenced the ΔMBL 16 and the heterogeneity of the results of the present systematic review of the literature. According to the retrospective study recently published by Galindo-Moreno et al, 62 the microstructure or the design of the implant adversely impacted the ΔMBL in peri-implant areas, possibly due to the generation of unbalanced tensile forces in the long-axis of the implant fixture.…”
Section: Discussionmentioning
confidence: 94%
“…These types of surface treatment may positively influence the osseointegration of dental implants, may upregulate the adhesion and proliferation of osteoblastic cells and may even increase the surface area available for attachment. 66,67,68,69 Another important point that must be considered is the presence of reduced implant platforms. These might have generated some of the differences detected among the manuscripts investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this repeated cleaning reduces cell adhesion as well as cell proliferation on titanium surface. Optimal surface properties, such as wettability, topography and chemistry have significant roles in osteoblastic cell adhesion [22], which is critical for the clinical success of dental implants. It is, however, difficult to distinguish which of these factors is responsible for the specific behavior of cells, as surface properties are interdependent on each other [23].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled formation of microstructures, particularly microgrooves, leads to cell orientation in the direction of the grooves, resulting in more effective bone regeneration on the implant surface 89 . However, according to another study, laser treatment leads increased roughness and wettability, but the biocompatibility of these surfaces is worse than that of machined surfaces 90 .…”
Section: Laser Treatmentmentioning
confidence: 99%